Genotoxicity assessment of the antimalarial compound artesunate in somatic cells of mice - Aquino, Ivani [UNESP]; Perazzo, Fabio Ferreira; Maistro, Edson Luis [UNESP] (Pergamon-Elsevier B.V. Ltd, 2011)
Artesunate is a derivate of artemisinin that is both an antimalarial agent and acts cytotoxically on tumor cells. Despite its therapeutic use, its in vivo genotoxic potential has still not been evaluated. This study, therefore, was an investigation into the effects of a single oral administration of artesunate with an in vivo comet assay that analyzed leukocytes from peripheral blood and liver cells, and a micronucleus (MN) assay of bone marrow cells from male Swiss mice. The artesunate was administered by oral gavage at doses of 5, 50 and 100 mg/kg. Cytotoxicity was assessed by scoring 200 consecutive polychromatic (PCE) and normochromatic (NCE) erythrocytes (PCE/NCE ratio). The results demonstrate that artesunate induced significant DNA damage only in liver cells and that high doses of artesunate caused an increase in the mean number of micronucleated polychromatic erythrocytes (MNPCE). Under our experimental conditions, artesunate showed weak genotoxic effects at low doses and clastogenic effects at high doses. The PCE/NCE ratio indicated no cytotoxicity. The data obtained suggest caution about either continuous or high-dose use of artesunate by humans. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Artesunate; Artemisinin derivate; Micronucleus test comet assay; Clastogenicity